Perioperative myocardial infarction: diagnostic clues and prevention - Larry Nichols (Autopsy and Case Reports, 2018)
The diagnosis of perioperative myocardial infarction can be missed if the pain is masked by postoperative analgesia and the possibility is not considered. This report is the case of a patient with a missed diagnosis of perioperative myocardial infarction. Myocardial injury and infarction from noncardiac surgery is currently the subject of intense interest and research. This report illustrates the importance of the diagnosis and suggests clues that can be used to make the diagnosis.